Normal range of anti–thyroid peroxidase antibody (TPO-Ab) and atherosclerosis among eu-thyroid population: A cross-sectional study. Issue 38 (18th September 2020) - Shimizu, Yuji; Kawashiri, Shin-Ya; Noguchi, Yuko; Nagata, Yasuhiro; Maeda, Takahiro; Hayashida, Naomi
Abstract : Abstract: Anti–thyroid peroxidase antibody (TPO-Ab), which is the known cause of autoimmune thyroid disease, enhances proinflammatory cytokine responses. Since low-grade inflammation is a known risk factor for atherosclerosis, a normal range of TPO-Ab (TPO-Ab negative) could be positively associated with atherosclerosis among participants with normal thyroid function. However, no study reported the association between normal range of TPO-Ab and atherosclerosis among eu-thyroid participants. A cross-sectional study was conducted with 1165 Japanese individuals with normal thyroid function (ie, normal range of free triiodothyronine [free T3] and free thyroxine [free T4]), aged 40 to 74 years, who participated in an annual health checkup in 2014. Among the study population, 115 were diagnosed as having atherosclerosis. A normal range value of TPO-Ab titer is revealed to be positively associated with atherosclerosis; sex, age, thyroid function (free T3 and thyroid-stimulating hormone), and known cardiovascular risk factor adjusted odds ratio and 95% confidence interval of atherosclerosis for logarithmic values of TPO-Ab was 2.23 (1.11, 4.47). When we limited the analysis to participants with normal levels of thyroid-stimulating hormone, this association became slightly stronger (2.65 [1.27, 5.51]). Among the eu-thyroid general population, a normal range of TPO-Ab titer is revealed to be positively associated with atherosclerosis. Even though a TPO-Ab titer is not clinically relevant and is not associated with autoimmune thyroid disease, it could influence endothelial remodeling including atherosclerosis.